A Theory of Soft Capture1. (10th April 2017) - Agrell, Per J.; Gautier, Axel
Abstract: In this paper, we propose an alternative model for capture that is based not on reciprocity but on congruence of interests between the firm and the regulator. A regulator is charged by a political principal to provide an imperfect signal for the type of a regulated firm. Only the firm can observe its type, and the production of a signal is costly. The firm can provide a costless alternative signal of lower accuracy to the regulator. In a self‐enforcing equilibrium, the regulator transmits the firm‐produced signal and saves information‐gathering costs, and the firm enjoys higher information rents.